Fuzzy implementation for temperature control on coffee roaster machine - Adhim, Fauzi Imaduddin; Akbar, Ilham Syahrial; Istiqomah, Fivitria; Priananda, Ciptian Weried; Rahayu, Lucky Putri; Musthofa, Arif (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
A roaster machine is a machine that is used for the process of determining the quality of the coffee it gets. The roaster machine at Puslitkoka still uses a manual process so that the Post Harvest operator always maintains the roasting process when researching to get quality coffee beans. The roaster machine at Puslitkoka is still maintained by the operator to stabilize the temperature of 140oC - 200oC with a time of 10 to 15 minutes to get the desired coffee beans. As a result of some of the problems above, it is necessary to develop a roaster machine. By adding a thermocouple sensor to measure the temperature that can move the servo valve to stabilize the gas output during the roasting process using the fuzzy logic method. When it reaches a temperature of 140oC the servo motor opens as input for coffee beans. All data obtained will be managed by Arduino Mega 2560. With the creation of this tool, it was found that the temperature control on the coffee roaster using the fuzzy method has a more minor average steady-state error of 5.85%. The conventional method has a larger error than fuzzy logic because the temperature increase is linear with time. For the required roasting time, the fuzzy method has a shorter time with an average of 549.67 seconds than the conventional method with an average time of 811.34 seconds.